AB0006 Mir-26a polymorphism is associated with susceptibility of rheumatoid and psoriatic arthritis. (12th June 2018) - Swierkot, J.; Sokolik, R.; Kozlowski, M.; Korman, L.; Wiland, P.; Bogunia-Kubik, K.
Abstract : Background: Serum levels of miR-26a has been reported to act as potential biomarker of rheumatic diseases. Objectives: The aim of the study was to analyse the genetic variation and expression of miR-26a as potential diagnostic and/or prognostic markers of rheumatoid diseases. Methods: The miR-26a polymorphism was examined in 111 patients with rheumatoid arthritis (RA), 86 patients with psoriatic arthritis (PsA) and 162 healthy blood donors that served as a control group. Genotyping for miR-26a rs7372209 was performed using a LightSNiP assay. For analysis of the miR-26a expression, RNA was isolated from sera of 15 RA patients (before and 3 months after anti-TNF treatment) and 10 controls (NucleospinmiRNA Plasma; MACHEREY-NAGEL GmbH and Co. KG) followed by cDNA synthesis (TaqMan MicroRNA Reverse Transcription Kit; Applied BiosystemsTM by Life Technologies) and Real-time PCR amplifications with hsa-miR-26a TaqMan specific and U6 snRNA control primers for each probe. The results were analysed using the (ΔΔCt) calculations. Results: It was found that the presence of miR-26a TT genotype (rs7372209) more than 5 times increases the risk of RA (OR=5.28, p=0.003) while the presence of CC homozygotes is associated with the risk of PsA (OR=1.77, p=0.037). There was no significant difference in the miR-26a serum levels between patients and controls. Also miR-26a serum levels did not significantly differed between RA patients before, 3 and 6 months after the implementation of biological therapy with TNF-alpha inhibitors. Conclusions: These results imply that miR-26a rs7372209 allelic variants differentially affect the risk of rheumatoid and psoriatic arthritis while anti-TNF biological treatment seems not to affect the miR-26a expression in RA patients. Disclosure of Interest: None declared